2022
DOI: 10.3390/molecules27082475
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Markers for Predicting Preeclampsia in the First Trimester of Pregnancy: A Retrospective Study

Abstract: We sought to identify the characteristic metabolite profile of blood plasma samples obtained from patients with preeclampsia. Direct high-resolution mass spectrometry was used to analyze samples from 79 pregnant women, 34 of whom had preeclampsia. We performed a comparative analysis of the metabolite profiles and found that they differed between pregnant women with and without preeclampsia. Lipids and sugars were identified as components of the metabolite profile that are likely to be associated with the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
1
1
Order By: Relevance
“…In contrast to our findings, Ilgisonis et al. demonstrated that de 18:1/20:0 CER was increased in plasma as early as the first trimester in pregnant women who develop PE ( 69 ). In the same group of patients with PE whose serum S1P was lower than in healthy controls, higher de 18:1/16:0 , de 18:1/18:0 , de 18:1/20:0 , and de 18:1/24:0 CER concentrations were found in both serum and placental tissue ( 70 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our findings, Ilgisonis et al. demonstrated that de 18:1/20:0 CER was increased in plasma as early as the first trimester in pregnant women who develop PE ( 69 ). In the same group of patients with PE whose serum S1P was lower than in healthy controls, higher de 18:1/16:0 , de 18:1/18:0 , de 18:1/20:0 , and de 18:1/24:0 CER concentrations were found in both serum and placental tissue ( 70 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Although metabolic biomarkers for PE are not yet widely used in clinical practice, this study and the existing literature shows that metabolomics can potentially become a clinical tool for predicting and diagnosing PE, as well as clarifying the etiology and pathogenesis of the disease ( 69 , 93 ). Our study shows that specific eicosanoids and sphingolipids can be accurately measured in the plasma of pregnant women and serve as early markers of the later development of PE with severe features regardless of patients being prescribed aspirin therapy (e.g., de 18:1/26:1 CER).…”
Section: Discussionmentioning
confidence: 89%